The effect of processing conditions on the mechanical and dielectric properties of epoxy foam - Wan Nur Fadilla Wan Hamad (School of Materials Engineering, 2011)
One of the purpose in this study is to investigate the effect of porosity on the mechanical, thermal and dielectric properties.